Water balance - stream water level and discharge from Miellejohka, 383 m a.s.l., 2017-04-06–2025-12-31 - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2026)
Stream water level measurements and discharge calculations from streams participating in the SITES Water and station base program including a constantly validated stream discharge relation curve. For further information on calculations and installation read COMMENT in the header of the data set, which guides to related document.
Abisko Scientific Research Station (2026). Water balance - stream water level and discharge from Miellejohka, 383 m a.s.l., 2017-04-06–2025-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/nT7cFkiHpeDnLfHEP46N3fDT
Keywords: Abisko Scientific Research Station; Discharge; Inland waters; Stream; Water level gauges; Time instant; Time instant; Stream level; Stream level; Standard deviation reading of SL within output interval; Standard deviation reading of SL within output interval; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap